2014
DOI: 10.1371/journal.pone.0086914
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Course Risk Factors for Childhood Obesity: The IDEFICS Case-Control Study

Abstract: BackgroundThe early life course is assumed to be a critical phase for childhood obesity; however the significance of single factors and their interplay is not well studied in childhood populations.ObjectivesThe investigation of pre-, peri- and postpartum risk factors on the risk of obesity at age 2 to 9.MethodsA case-control study with 1,024 1∶1-matched case-control pairs was nested in the baseline survey (09/2007–05/2008) of the IDEFICS study, a population-based intervention study on childhood obesity carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
88
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 58 publications
10
88
0
2
Order By: Relevance
“…Similar results are reported in a European study which investigated ante-, peri-and postnatal risk factors on risk of obesity in children at 4r and 8 years of age [26]. GWG >25 kg posed after adjustment a twofold risk of obesity for the offspring.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results are reported in a European study which investigated ante-, peri-and postnatal risk factors on risk of obesity in children at 4r and 8 years of age [26]. GWG >25 kg posed after adjustment a twofold risk of obesity for the offspring.…”
Section: Discussionsupporting
confidence: 87%
“…An association between maternal BMI and/or GWG and the BMI of offspring have been investigated in some large cohort studies [25][26][27]. A Norwegian study found a positive association between both maternal pre-pregnancy BMI and GWG and the mean BMI of the offspring at 3 years of age [25].…”
Section: Discussionmentioning
confidence: 99%
“…Weight data were collected on 756 women. Only 385 women had weights measured in all three study assessment periods (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) weeks, 20+1 to 32 weeks and >32 weeks gestation) while 427 women had weights measured in Period 3. Individual…”
Section: Introductionmentioning
confidence: 99%
“…Based on limited data however correlations between gestational weight gain and offspring birth weight as well as childhood obesity have been demonstrated (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This is conceivable because healthy pregnant women may compensate for much of the assumed increased energy needs by selecting less demanding physical activities (5). Recommending additional energy intake may therefore contribute to the increasing prevalence of excessive weight gain in pregnancy, a risk factor for gestational diabetes and offspring obesity (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%